Fenómenos de sedimentação e transporte - início do movimento - Elsa Carvalho (2006)
The present work is a link between the previously made boundary layers studies and the future deep study of the beginning of sediment motion. Using the obtained results for smooth walls, the possibility of occurrence of sediment motion has been evaluated by means of known criteria, for uniform particle beds and for the same flow conditions. Those results have been confirmed through experimental measurements, carried out under the same flow conditions. Additional tests using particle motion flow conditions have been made and some results are also presented and will be developed in a future work.